Evaluation of Lightning-Related Deaths - Yılmaz, Rıza; Bulut, Ragıp Erkut; Özer, Erdal; Balkay, Mustafa; Özdemir, Nazım; Gürpınar, Süleyman Serhat (The Bulletin of Legal Medicine, 2007)
Lightning is an atmospheric discharge of electricity between clouds and the earth. Death records Council of Forensic Medicine 1. Specialty Committee between 1998 and 2006 were included and reviewed retrospectively. 15 cases, the cause of deaths are determined as lightning-related were found and these cases were evaluated with regard to age, sex, job, crime scene and internal, external and micropathologic findings. Lightning strike especially occurs in rainy afternoons of spring and summer seasons. Of our cases, 3 have occurred in summer, 6 in spring and the rest 6 in autumn. Lightning-related deaths may reveal none of pathologic findings or no patog-nomonic features, such as eudema, hyperemia, congestion and hemorrhage can be described in autopsy. For this reason crime scene investigation is very important in these cases. Age of our cases ranged from 3 years old to 53 years old. Lightning caused deaths occurs frequently among agricultural workers and sailors in developing and underdeveloped countries and occur frequently among natural sports dealers in developed countries. As a result, a careful examinations of internal and external findings due to lightning accompanied by a wide crime scene investigation is very important. Crime scene investigation must include weather conditions, thunder, stormy, also clothes parts-house-tree damages, group deaths of animals and other results and evidences of a lightning must be examined carefully. Key words: Lightning injury, crime scene investigation, autopsy, forensic sciences